INTERACTION OF EUROPIUM CHELATES WITH LIPID MONOLAYERS - V. Trusova; A. Yudintsev; O. Kutsenko; O. Pakhomova; R. Volinsky; G. Gorbenko; T. Deligeorgiev; P. Kinnunen (East European Journal of Physics, 2015)
The ability of novel anticancer drug candidates, europium coordination complexes (EC), to penetrate the phospholipid monolayer composed of dimyristoylphosphatidylcholine (DMPC) was studied using Langmuir monolayer technique. EC were found to insert readily into the lipid monolayer with penetration extent being dependent on both drug structure and initial surface pressure of the lipid film. Evaluation of the limiting surface pressure revealed that all drugs are capable of inserting into the cellular membranes.